Tracheobronchopathia osteoplastica: a clinical case report of a 63-year-old man - Lai, Jing; Deng, Yingli; He, Qingmin (Frontiers in Medicine, 2024)
Tracheobronchopathia osteoplastica (TO) is a rare benign lesion of the airways, characterized by multiple nodular proliferations of bone and/or cartilaginous tissue in the submucosa of the trachea and bronchi. In this paper, we present a case of a 63-year-old male patient who was admitted to the hospital due to cough and blood in his sputum. The patient was diagnosed with TO through examination and pathological biopsy. The exact pathogenesis of this disease remains unclear, but it may be related to multiple factors such as chronic infection and inflammation. The clinical manifestations are diverse, with no symptoms or only mild cough in the early stage, and persistent cough, dyspnea, and other symptoms may appear as the disease progresses. Diagnosis mainly relies on pathological biopsy, while treatment is mainly symptomatic, including inhalation of glucocorticoids, airway interventional therapy, and stent placement. Overall, TO progresses slowly and has a good prognosis, but early diagnosis and elimination of predisposing factors are crucial for treatment.